Library Information System Implementation MTs Ittihaadul Umam Depok Case Study - Ahmad Ishaq; Achmad Sumbaryadi; M. Ikhsan Saputro; Rame Santoso; Toni Sukendar (Universitas Mohammad Husni Thamrin, 2026)
Many organizations encounter challenges in managing information effectively and efficiently. A significant number of data management processes are still performed manually, which increases the risk of errors and information loss. Similar to libraries, which require quick and accurate access to information, this study aims to implement a web-based library information system for the MTs Ittihaadul Umam Depok library. The research employs the Rapid Application Development (RAD) methodology, which includes stages such as business modeling, data modeling, process modeling, application creation, and testing and turnover. At this stage, an analysis of the book management needs at MTs Ittihaadul Umam Depok was conducted to guide the system development. Based on the research findings and the challenges faced at the MTs Ittihaadul Umam Depok library, designing and implementing an integrated web-based library information system is expected to simplify the process of borrowing and returning books for all library members. Additionally, it will assist library staff in managing library data more efficiently and help the school advance its technological capabilities.